Design of Automatic Feeder for Shrimp Farming Based on Internet of Things Technology - Arditya, Ilham; Setyastuti, Tri Ari; Islamudin, Fikri; Dinata, Iskandar (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
In shrimp farming, feeding is an important activity to achieve good shrimp growth. Manual feeding manually using hand is less effective due to unequal food distribution. Thus, an automatic feeder is required to dispense feed at predetermined time. The advantages of automatic feeder are cost-effective, low labour requirement, and can be applicable for large volumes of feed. Design of automatic feeder machine can influence the capacity and time controlling of the feeder. In this research, the automatic feeder was designed using a controlling time system based on Internet of Things (IoT) technology. During plant trial, The automatic feeding was scheduled at 7 am, 11 am, 4 pm, and 8 pm. This machine could throw shrimp food homogeneously up to 10 m far for 2,500 m2 pond area. In shrimp farming, distribution of shrimp food in predetermined time becomes an important rule to achieve good shrimp growth.